Highly reliable GIGA-sized synthetic human therapeutic antibody library construction - Huang, Chao-Yang; Lok, Ying-Yung; Lin, Chia-Hui; Lai, Szu-Liang; Wu, Yen-Yu; Hu, Chih-Yung; Liao, Chu-Bin; Ho, Chen-Hsuan; Chou, Yu-Ping; Hsu, Yi-Hsuan; Lo, Yu-Hsun; Chern, Edward (Frontiers in Immunology, 2023)
Background: Monoclonal antibodies (mAbs) and their derivatives are the fastest expanding category of pharmaceuticals. Efficient screening and generation of appropriate therapeutic human antibodies are important and urgent issues in the field of medicine. The successful in vitro biopanning method for antibody screening largely depends on highly diverse, reliable and humanized CDRs library. To rapidly obtain potent human antibodies, we designed and constructed a highly diverse synthetic human single-chain variable fragment (scFv) antibody library greater than giga size through phage display. Herein, the novel TIM-3-neutralizing antibodies with immunomodulatory function derived from this library were as an example to demonstrate the library’s potential for biomedical applications. Methods: The library was designed with high stability scaffolds and six complementarity determining regions (CDRs) tailored to mimic human composition. The engineered antibody sequences were optimized for codon usage and subjected to synthesis. The six CDRs with variable length CDR-H3s were individually subjected to β-lactamase selection and then recombined for library construction. Five therapeutic target antigens were used for human antibody generation via phage library biopanning. TIM-3 antibody activity was verified by immunoactivity assay. Results: We have designed and constructed a highly diverse synthetic human scFv library named DSyn-1 (DCB Synthetic-1) containing 2.5 × 1010 phage clones. Three selected TIM-3-recognizing antibodies DCBT3-4, DCBT3-19, and DCBT3-22 showed significant inhibition activity in TIM-3 reporter assays at nanomolar ranges and binding affinities in sub-nanomolar ranges. Furthermore, clone DCBT3-22 was the superior candidate with good physicochemical property and a purity of more than 98% without aggregation. Conclusion: The promising results illustrate not only the potential of the DSyn-1 library for biomedical research and applications but the therapeutic potential of three novel fully human TIM-3-neutralizing antibodies in the future.